HVDC transformer insulation system: Present research, trends, challenges, and prospects - Muhammad Rafiq; Muhammad Shafique (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
High-voltage direct current (HVDC) has attained significant consideration owing to numerous valuable characteristics, for instance, lowest transmission losses, improved stability, and control operation. The HVDC transformer is one of the significant elements in the HVDC transmission system. Thus, it is noteworthy to ensure the optimal working of this vital component for the reliability, efficiency, and safety of power grid. The mineral oil (MO) is generally applied together with paper as an insulating medium in a majority of HV apparatus. For the insulation of power transformers, the oil/paper insulating system has demonstrated itself for several years as a major component. As a result of continuous growth in high-performance semiconductor components, HVDC power transmission becomes more and more significant due to key gains associated with these systems. This may develop challenges specifically in the case of converter transformers as the insulation is not subjected entirely to a simple AC stress. Based on the topology, the transformer insulation is exposed to a combined voltage stress (both AC with DC). This, conversely, leads to significant impacts and encounters regarding the electric stress of insulating elements of oil and paper. In the context of simple AC voltage stress, capacitive field distribution occurs corresponding to permittivities. Conductivities in the case of AC electric field are not significant nonetheless initiate trivial dielectrics losses. In the event of DC stress, they are pivotal as field distribution develops depending on their values. In contrast to AC stress, it results in a decrease of stress on oil however to a rise in stress on insulating paper. Through switching activities or polarity reverses, a shift from the dielectric displacement field to the steady-state electric DC field occurs. This could turn challenging specifically in the case of converter transformers as the insulation is not subjected solely to a simple AC stress. Polarization mechanisms, particularly interfacial polarization, and noticeably contrasting polarization durations between the materials of oil and paper should be considered. This article exhibits a thorough review of the HVDC transformer insulation system. The importance of this article lies in outlining the previous research, arranging the research core, and inducements, and forecasting imminent research trends. Furthermore, it describes an independent assessment of the challenges, opportunities, scenarios, and restraints being faced in developing the HVDC transformer insulation system more efficiently are clearly stated. The information documented in this review is projected to present an essential guideline for potential research in HVDC transformer insulation systems. This article is valuable for both academia and industry experts as it summarizes meaningful outlines of research in the field.